THE RULES OF SETTING UP AND FUNCTIONING FISH PRODUCERS’ ORGANISATIONS AND INTERTRADE ORGANISATIONS IN THE LIGHT OF THE ACT (OCTOBER 10TH, 2002) - Zieziula, Jolanta (Acta Scientiarum Polonorum. Oeconomia, 2003)
The Act of October 10th, 2002 Of fish market organisation and change of the act of sea fishery gives opportunities for setting up fish producers’ organisations and intertrade organisations in accord to European Union standards. In the article the necessity of establishing such organisation has been shortly discussed. What is more, the definitions of the organisations and the conditions of registering them have been presented. Moreover, there have been described decisions of Ministry of Agriculture those have to be done, so that the organisations could function and take profits from the law. However, many matters were left to later settlement, which is one of threatens for setting up fish producers’ organisations and intertrade organisations. In the paper have been also shown other threatens, including the lack of government help.